Socio-Material Archaeological Networks at Çatalhöyük a Community Detection Approach - Mazzucato, Camilla (Frontiers in Digital Humanities, 2019)
Vast in scale and densely inhabited, Late Neolithic Near Eastern megasites have been variously considered in relation to urbanity. Often viewed as failed experiments on the path to proper urbanism or proto-urban sites, these settlements reveal few signs of hierarchical social stratification despite their large size; as such, they represent a challenge for the understanding of early processes of community formation and social integration. Drawing upon a wide range of data and using socio-material network analysis as a methodological tool, this paper explores the way the late Neolithic site of Çatalhöyük was organized internally and specifically the way individual houses were embedded in the wider social fabric of the site. This study sheds light on the nature of the networks of social engagement and affiliation that emerge in the Holocene within large early agricultural communities and the way such networks were manifested.